Genetic diversity of 15 autosomal short tandem repeats loci using the AmpFLSTR(®) Identifiler™ kit in a Bhil Tribe Population from Gujarat state, India - Chaudhari, Ramesh R. (Indian J Hum Genet, 2014)
MATERIALS AND METHODS: The genetic diversity and forensic parameters based on 15 autosomal short tandem repeats (STR) loci; D8S1179,D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317,D16S539, D2S1338, D19S433, vWA, TPOX, D18S51,D5S818, and FGA in AmpFLSTR® Identifiler™ kit from Applied Biosystems, Foster City, CA, USA were evaluated in saliva samples of 297 unrelated individuals from the Bhil Tribe population of Gujarat state, India to study genetic diversities and relatedness of this population with other national and international populations. RESULTS: Statistical analysis of the data revealed all loci were within Hardy-Weinberg Equilibrium expectations with the exception of the locus vWA (0.019) and locus D18S51 (0.016). The neighbour joining phylogeny tree and Principal Co-ordinate Analysis plot constructed based on Fst distances from autosomal STRs allele frequencies of the present study and other national as well as international populations show clustering of all the South Asian populations in one branch of the tree, while Middle Eastern and African populations cluster in a separate branch. CONCLUSION: Our findings reveal strong genetic affinities seen between the Indo-European (IE) speaking Bhil Tribe of Gujarat and Dravidian groups of South India.